MALTREATMENT IN THE SOCIAL ENVIRONMENT - Nanda Aisyah (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
The act of persecution whether committed against a person or several people is a prohibited act and this is not justified because according to the Law of the Republic of Indonesia. act is prohibited and is not justified because according to the Criminal Code the act of persecution is categorized as a criminal offense. The act of persecution is categorized as a criminal offense. Maltreatment is an act with the aim of causing pain or injury to another person, the perpetrator wants the result of an act of harm or torture. The perpetrator wants the result of an act of harm or torture. Maltreatment, whether verbal, physical, or psychological, impacts on well-being and creates an environment of psychological, impacts onwell-being and creates an unhealthy social environment. This research This study aims to measure the impact of maltreatment on victims and evaluate the effectiveness of legal legal protection in Indonesia. Data was collected through a literature study. This research shows that the impact of maltreatment includes psychological, physical and social. This article also outlines prevention and intervention strategies that involve active participation from various parties, including individuals, families, institutions and the government. This study is expected to serve as a basis for more effective policies and policies and programs that are more effective in creating a social environment that is inclusive and free from maltreatment. and provide legal protection for victims of maltreatment. From the legal side, there are several barriers to the implementation of legal protection, such as lack of reporting and a lack of understanding of the law by relevant parties.